OUTCOMES OF ULTRASOUND-MONITORED TREATMENT OF DIVELOPMENTAL DYSPLASIA OF THE HIP GRAF TYPE II - Djoleva Tolevska, Roza; Matveeva, Niki; Georgieva, Daniela; Bojadzieva Stojanoska , Biljana (Sanamed, 2022)
Introduction: The management of developmental dysplasia of the hips (DDH) type Graf IIa is still controversial. This study aims to examine the outcomes of ultrasound-monitored Pavlik harness treatment, as well as the effects of associated factors, such as gender, side of DDH, the age at the treatment start, and laterality on the treatment outcomes in different Graf type II subtypes. Methods: A cohort retrospective investigation was performed on 88 ultrasound-screened infants or 125 hips diagnosed with Graf type II dysplasia during a six-month period at a single institution, the University Clinic for Orthopedic Surgery, Skopje. Subsequently, 47 infants (18 boys, 29 girls) or 73 hips who underwent Pavlik harness treatment with at least one follow-up throughout treatment monitoring were included in this study. Results: The treatment success rate of the right DDH Graf type IIa (-) was higher (70.8%) compared to the rate of success (50%) in the treatment of left Graf type IIa (-) hips. The mean age of the infants at the treatment start in successfully treated Graf type IIa (-) hips was lower (9.12 ±2.27 weeks) compared to the age of the infants with treatment failure at the last follow-up (11.33 ±3.06 weeks), P= 0.04. Conclusion: The age of treatment initiation and the side of DDH were the most relevant factors related to the treatment outcome. Infants with maturational deficit hips, Graf type IIa (-), should undergo early initiated, carefully guided, and monitored Pavlik harness treatment.